2012
DOI: 10.2495/deb120141
|View full text |Cite
|
Sign up to set email alerts
|

Medium term fluvial island evolution in relation with flood events in the Piave River

Abstract: River islands could be defined as discrete areas of woodland vegetation surrounded by either water-filled channels or exposed gravel which exhibits some stability, and remain exposed during bunk-full flows. Islands are important from morphological, functional, and ecological points of view. The aim of the present study is to analyze the dynamics of stable, young and pioneer islands in the Piave River, which suffered intense and multiple human impacts especially due to dam building and in-channel gravel mining.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…On the other hand, along the Tagliamento river there is a higher difference between the sizes of the stable islands and the other two kinds, this is probably due to the fact that only the more established islands are able to resist to the very common flood events that could happen different times per year moving huge volumes of sediments . These observations matched with those made by different authors (Bertoldi et al, 2009;Comiti et al, 2011;Picco et al, 2012a) wherein the island dynamics were found to be strictly associated to the occurrence of major floods (RI > 10-15 years), which are the only ones able to generate substantial island erosions.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…On the other hand, along the Tagliamento river there is a higher difference between the sizes of the stable islands and the other two kinds, this is probably due to the fact that only the more established islands are able to resist to the very common flood events that could happen different times per year moving huge volumes of sediments . These observations matched with those made by different authors (Bertoldi et al, 2009;Comiti et al, 2011;Picco et al, 2012a) wherein the island dynamics were found to be strictly associated to the occurrence of major floods (RI > 10-15 years), which are the only ones able to generate substantial island erosions.…”
Section: Discussionsupporting
confidence: 80%
“…As expected, the established ones lie at higher elevation. This is due to the fact that older vegetation growing on established islands allows the deposition of fine sediments which, in turns, enhances the conditions for vegetation growth, providing even better circumstances for the vegetation to establish on stable islands (Picco et al, 2012a). The flood control (by dams) and the sediment recruitment control (by embankments), can be the factors that trigger the higher difference in the ground elevation between the three island types along the strongly affected Brenta river.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ceasing of gravel extraction in the late 1990s seems to have determined a reversal in the evolutionary trend, with evidence of vegetation erosion/channel widening (Comiti et al [15]). This complex series of planimetric and vertical adjustments, and especially the recent active channel widening tendency may explain why "mature" patches lie at elevations similar to areas covered with the most pioneer plant communities (Picco et al [24]). …”
Section: Resultsmentioning
confidence: 99%
“…Comiti et al (2011) estimated that ten years represents the return interval of the peak discharge able to considerably modify the fluvial planimetric shape, especially of floodplains and islands. This is confirmed also by island reduction processes that take place due to flood events of considerable magnitudes (Comiti et al, 2011;Picco et al, 2012aPicco et al, , 2012bMao et al, 2012). Because of the importance of highmagnitude floods (RI>5 years) in shaping the river, a question arises as to the actual effectiveness of near-bankfull flows (RI~1.5 years) in determining the morphology of the Brenta River.…”
Section: Morphological Adjustments Along the Brenta Rivermentioning
confidence: 72%